Estimating Above-Ground Fuel Biomass in Young Calabrian Pine (Pinus brutia Ten.) - Bilgili, Ertugrul; Kucuk, Omer (American Chemical Society (ACS), 2008)
Crown fuel biomass is of great importance in the field of forest-fire science. In this study, regression equations were developed for predicting needle, branch, and total biomass of young calabrian...
Keywords: 15. Life on land